Microbial Quality Of Raw And Pasteurized Milk Samples Collected From Different Places Of Warangal District, (A.P.) India - G. SRUJANA,; A.RAJENDER REDDY,; V. KRISHNA REDDY,; S. RAM REDDY, (International Journal of Pharma and Bio Sciences, 2011)
Milk is nutritious and essential food for human beings and also serves as good medium for microbial growth and contamination 240 raw milk samples and 72 pasteurized milk samples from different places of Warangal District for a period of six months were analysed for microbial quality. Among the raw milk samples only 19.1% of samples were good quality and 28.3% are very poor quality. In the pasteurized milk samples 81.9% of samples were good for human consumption. The bacteria isolated from milk samples includes Lactobacilli, Staphylococcus aureus, Escheritia coli, Bacillus subtilis , Salmonella typhi, and feacal coliforms.